Near infrared organic light emitting devices based on a new erbium(iii) β-diketonate complex: synthesis and optoelectronic investigations. Issue 30 (27th March 2017) - Ahmed, Zubair; Aderne, Rian E.; Kai, Jiang; Resende, Jackson A. L. C.; Padilla-Chavarría, Helmut I.; Cremona, Marco
Abstract : This paper deals with the synthesis of a new near infra-red emitting Er(iii ) β-diketonate complex of low coordinate structure, its characterisation and fabrication of organic light emitting diode using the complex as emitting layer. Abstract : An in situ reaction of two optoelectronically active organic ligands (anionic thenoyltrifluoroacetylacetone, tta −, and neutral triphenylphosphine oxide, tppo) with erbium(iii ) ion in the presence of a base yielded a new erbium complex, [Er(tta)3 (tppo)]. The solid and solution structure of the complex was established by X-ray crystallography, NMR, ESI-MS, FTIR, TGA and Raman spectroscopy. They indicate that the Er(iii ) ion is coordinated to seven oxygen atoms of three tta ligands and one tppo ligand in a monocapped octahedral geometry. The Judd–Ofelt parameters of the complex were determined by a least squares fitting and dealt with its chemical structure. On UV excitation through ligand mediation, the complex shows the characteristic near-infrared emission of the corresponding Er(iii ) ion at 1534 nm. Furthermore, a near infra-red organic light emitting diode (NIR-OLED) was fabricated with structure: ITO/[ N, N ′-bis(naphthalen-2-yl)- N, N ′-bis(phenyl)benzidine]/[Er(tta)3 (tppo)]/[2, 2′, 2′′-(1, 3, 5-benzinetriyl)-tris(1-phenyl-1- H -benzimidazole)]/LiF/Al. This device, with maximum applied voltage of 23 V, shows a total quenching of visible emission and electroluminescence in the C-band region (1534 nm) which is suitable for third communication window applications in fiber optics. Finally, an organic diode was fabricated to determine charge carrier mobility of the complex using a steady-state method.